Intermediate Outcomes of Staged Tetralogy of Fallot Repair. Issue 6 (November 2019) - Mahajan, Poonam; Ebenroth, Eric S.; Borsheim, Kirsten; Husain, Sabena; Bo, Na; Herrmann, Jeremy L.; Rodefeld, Mark D.; Turrentine, Mark W.; Brown, John W.; Patel, Jyoti K.
Background: The optimal surgical strategy for tetralogy of Fallot (TOF) repair in neonates and young infants requiring early surgical intervention remains controversial. Our surgical center follows the uniform strategy of a staged approach with initial systemic-to-pulmonary artery shunt the majority of time when early surgical intervention is required. We characterized a contemporary cohort of patients with TOF with pulmonary stenosis (PS) undergoing staged repair in order to determine the rate of pulmonary valve-sparing repair (PVSR), growth of the pulmonary valve annulus and pulmonary arteries, postoperative morbidity and mortality, and need for reintervention. Methods: We retrospectively studied patients with TOF/PS who underwent staged repair from 2000 to 2017. Surgical details, postoperative course, and reinterventions were noted. Echocardiographic measurements and Z-score values of pulmonary valve annulus, main pulmonary artery (MPA), right pulmonary artery (RPA), and left pulmonary artery (LPA) diameters were evaluated. Results: Of the 59 patients with staged TOF/PS, PVSR was performed in 25 (42%). There was a 5% incidence of postoperative arrhythmia. The Z-scores of MPA, RPA, and LPA were significantly higher before complete repair when compared to before palliative shunt. The 5 and 10-year survival rates were both 93%, and the probability of freedom from reoperation at 5 and 10 years was 87% and 82%, respectively. Conclusions: Staged repair of TOF in young symptomatic infants results in 42% receiving PVSR, pulmonary artery growth, low incidence of postoperative arrhythmia, and relatively low rate of reoperations.